2002
DOI: 10.1021/bi012116t
|View full text |Cite
|
Sign up to set email alerts
|

Mispairing of the 8,9-Dihydro-8-(N7-guanyl)-9-hydroxy-aflatoxin B1 Adduct with Deoxyadenosine Results in Extrusion of the Mismatched dA toward the Major Groove

Abstract: The G --> T transversion is the dominant mutation induced by the cationic trans-8,9-dihydro-8-(N7-guanyl)-9-hydroxy-aflatoxin B(1) adduct. The structure of d(ACATC(AFB)GATCT).d(AGATAGATGT), in which the cationic adduct was mismatched with deoxyadenosine, was refined using molecular dynamics calculations restrained by NOE data and dihedral restraints obtained from NMR spectroscopy. Restrained molecular dynamics calculations refined structures with pairwise rmsd<1 A and a sixth root R1x factor between the refine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 70 publications
(136 reference statements)
2
13
0
Order By: Relevance
“…Although there are cases in which the adduct interacts with the minor (12, 13) or the major groove (14,15) of the double helix, in most cases the interaction occurs through intercalation between the surrounding base pairs (13, 16 -32). In many cases, the intercalation occurs from the major groove side (21,27,(31)(32)(33), resembling the conformation adopted by the cholesterol adducts studied in this paper. Displacement of the opposite base out of the helix is rather common, and in many cases the unpaired base is shifted toward the major groove.…”
Section: Molecular Recognition Properties Of the Damaged Dnas-mentioning
confidence: 67%
“…Although there are cases in which the adduct interacts with the minor (12, 13) or the major groove (14,15) of the double helix, in most cases the interaction occurs through intercalation between the surrounding base pairs (13, 16 -32). In many cases, the intercalation occurs from the major groove side (21,27,(31)(32)(33), resembling the conformation adopted by the cholesterol adducts studied in this paper. Displacement of the opposite base out of the helix is rather common, and in many cases the unpaired base is shifted toward the major groove.…”
Section: Molecular Recognition Properties Of the Damaged Dnas-mentioning
confidence: 67%
“…AFB 1 -FAPY adducts have also displayed higher mutagenic potency and stronger blocking effects on DNA replication relative to their molecular predecessors (AFB 1 -N7-Gua adducts) 22. Nuclear magnetic resonance studies have demonstrated that AFB 1 -FAPY adducts have a more subtle effect on DNA architecture and a pronounced effect on the melting temperature of the DNA duplex than AFB 1 -N7-Gua adducts41, 42. These properties enable the AFB 1 -FAPY adducts to evade DNA repair and exhibit great mutagenic potentials 40, 43, 44.…”
Section: Discussionmentioning
confidence: 99%
“…AFB 1 is among the most potent mutagens implicated in human carcinogenesis , . Moreover, it is mutagenic in bacteria and carcinogenic in fish, and it is a hepatocarcinogen in rodents , . AFB 1 has also been considered a biological/chemical weapon, e.g., in 1989 in Iraq .…”
Section: Introductionmentioning
confidence: 99%
“…AFB 1 exo-8,9-epoxide also reacts with DNA, evidently after intercalation (1). Reaction occurs with high regiospecificity at the N7 position of guanine (Gua) residues, yielding the trans-8,9-dihydro-8-(N 7 -guanyl)-9-hydroxyaflatoxin adduct (4). The proposed reaction mechanism is depicted in Figure 1.…”
Section: Introductionmentioning
confidence: 99%